Perlindungan Hukum Terhadap Kedaulatan Negara Dari Ancaman Proxy War - Wada, Igam Arya (Universitas Muhammadiyah Jember, 2019)
Proxy war is a form of non-military war by using a non-state actor instead of a particular party, to avoid a direct dispute. One of the non-state actors who are vulnerable to use foreign parties to launch proxy war in Indonesia is the existence of radical organizations either with radical action or radical thinking. In addition, the spread of provocative information and hoax can easily spread through the mass media and social media today, causing problems to the integrity of the Unitary Republic of Indonesia. So far Indonesia has no laws that can counter the nirmiliter threat such as proxy war so that Indonesia is in need of a law that can be used as a preventive effort to protect the state sovereignty against the existence of proxy war in Indonesia. In addition, the public understanding of Pancasila ideology as a way of life should be a necessity in the life of nation and state is still low, so it will be difficult to ward off another ideologies such as radicalism that developed in Indonesia.